Morphogenesis and Organogenesis to Hatching of the Green Octopus, Octopus hubbsorum: A Species That Includes a Paralarval Stage in Its Life Cycle - Maritza García-Flores; Marcial Arellano-Martínez; Carlos A. Aguilar-Cruz; M. Carmen Rodríguez-Jaramillo (Diversity)
This work describes the morphological changes during embryonic development and pre-hatching organ development of Octopus hubbsorum, a species with a paralarval phase in its life cycle. The morphogenesis of O. hubbsorum begins simultaneously with the first reversion, a typical characteristic of octopuses, along with the development of the embryonic shape and structure. However, this species hatches with only three well-developed suckers. Organogenesis starts after the first embryonic reversion, with the development of the eyes, optic lobes, digestive gland, arms, and mantle. The branchial and central hearts show optimal development before the second reversion. The ink sac develops in the late stages (after the second reversion), while the stomach and crop are evident only after hatching and continue to develop until the first feeding. Newly hatched organisms show a complete development of the nervous, respiratory, circulatory, and integumentary systems. During the paralarval phase, O. hubbsorum undergoes major morphological and physiological changes until it reaches the subadult phase and develops the reproductive organs. This study highlights important organogenic differences compared to species with planktonic and benthic hatchlings. Further studies are needed in species with different life strategies to expand our knowledge of the developmental biology of cephalopods.